A Relativistic Bremsstrahlung/Inverse Compton Origin for 2EG J1857+0118 Associated with Supernova Remnant W44 - de Jager, O. C.; Mastichiadis, A. (1997)
We show that relativistic bremsstrahlung and inverse Compton scattering of radio-emitting electrons can easily account for the observed γ-ray spectrum of 2EG J1857+0118 if the field strength in the shell is below ~30 μG. This source is located at the eastern border of the composite SNR W44, where the expanding radio shell is interacting with a dense molecular cloud. The nondetection of this remnant above 250 GeV implies a cutoff or steepening in the electron spectrum above ~100 GeV. The E-1.66 spectrum of this radio/γ-ray-emitting electron component is too flat to have its origin in standard first-order Fermi acceleration, but electron injection into the shell by the pulsar PSR B1853+01 over the 2 × 104 yr lifetime may explain why the Crab-like radio spectrum (Sν ~ ν-0.33) is about the hardest of all shell-type remnants. The injected energy would be sufficient to account for the required energy of 6 × 1049 ergs if the initial spin-down power of PSR B1853+01 was about 10 times larger than the present spin-down power of the Crab pulsar. A steeper Fermi electron component may be present, but the observational data are not constraining enough to provide a meaningful limit on the presence of an additional ~E-2 shell-type electron component. The predicted γ-ray contribution from high-energy proton-gas interactions is about 20% of the observed EGRET flux above 100 MeV, which confirms our conclusion that the γ-ray emission from W44 is dominated by a leptonic component.
Keywords: acceleration of particles; gamma rays: theory; ISM: Individual: Alphanumeric: W44; ISM: supernova remnants; Radiation Mechanisms: Nonthermal; Stars: Pulsars: Individual: Alphanumeric: PSR B1853+01